A two step technique to remove the secondary phases in CZTS thin films grown by sol - gel method. Issue 8 (1st June 2019) - Ashfaq, Arslan; Jacob, Jolly; Bano, N.; Nabi, M. Ajaz Un; Ali, A.; Ahmad, W.; Mahmood, K.; Arshad, M.I.; Ikram, Salma; Rehman, U.; Amin, N.; Hussain, S.
Abstract: In this study, we have used a two step method to eliminate the secondary phases in the CZTS thin films grown by sol-gel technique. In the first step, CZTS thin films were grown on different substrates [ITO coated glass (ITO), Soda Lime Glass (SLG), multi-crystalline Silicon (m-Si) and crystalline Silicon (c-Si)] to investigate the optimal substrate for the growth of CZTS with minimum number of secondary phases. XRD, SEM and Raman spectroscopy measurements suggested that the sample grown on ITO substrate has only ZnS and Cu2 S secondary phases meanwhile samples grown on mc-Si and C-Si have a number of secondary phases. Due to its smooth surface and single crystalline nature, ITO facilitates the CZTS growth with minimum secondary phases. Therefore, we have used ITO substrate for the further growth of CZTS thin films in the second set of samples. In the second step the previously grown CZTS/ITO samples were annealed in sulphur atmosphere at 500 °C using a tube furnace for different time durations of 20, 40, 60 and 80 min. The characterization data suggested that ZnS secondary phase was still present in the samples which are annealed for 20–60 min while other secondary phase (Cu2 S) was eliminated. Finally the ZnS phase also vanished when the annealing time duration was increased to 80 min. The disappearing of secondary phases was maybe due to suppressing the off-stiochiometric composition by increasing the sulpurizing time.